Limited Utility of ITPA Deficiency to Predict Early Anemia in HCV Patients with Advanced Fibrosis Receiving Telaprevir - Aghemo, Alessio; Grassi, Eleonora; Rumi, Maria Grazia; D'Ambrosio, Roberta; Galmozzi, Enrico; Degasperi, Elisabetta; Castaldi, Davide; Soffredini, Roberta; Colombo, Massimo (PloS one, 2014)
Severe anemia is a common side effect of Pegylated Interferon + Ribavirin (PR) and Telaprevir (TVR) in hepatitis C virus (HCV) genotype 1 patients with advanced fibrosis or cirrhosis (F3-F4). Inosine triphosphatase (ITPA) genetic variants are associated with RBV- induced anemia and dose reduction. To test the association of ITPA polymorphisms rs1127354 and rs7270101 with hemoglobin (Hb) decline, need for RBV dose reduction (RBV DR), erythropoietin (EPO) support and blood transfusions during the first 12 weeks of TVR triple therapy. 69 consecutive HCV-1 patients (mean age 57 years) with F3-F4 who received PR and TVR were genotyped for ITPA polymorphisms rs1127354 and rs7270101. Estimated ITPA deficiency was graded on severity (0-3, no deficiency/mild/moderate/severe). ITPA deficiency was absent in 48 patients (70%), mild in 12 (17%) and moderate in 9 patients (13%). Mean week 4 Hb decline was higher in non ITPA deficient patients (3,85 g/dL) than in mildly or moderately ITPA deficient patients (3,07 g/dL and 1,67 g/dL, p<0.0001). Grade 3-4 anemia developed in 81% non ITPA deficient patients versus 67% mild deficient and 55% moderate deficient patients (p = ns). Grade of ITPA deficiency was not associated with RbvDR (no deficiency: 60%, mild: 58%, moderate: 67%; p = ns), EPO use (no deficiency: 65%, mild: 58%, moderate:56%; p = ns) or need for blood transfusion (no deficiency: 27%, mild: 17%, moderate: 33%; p = ns). In patients with F3-F4 chronic hepatitis C receiving TVR based therapy, ITPA genotype does not impact on the management of early anemia.